EUROPEANIZATION AND DEVELOPMENT: USING OPEN REGIME THEORY TO ASSESS LITHUANIA’S POST-EU ACCESSION - Maniokas, Klaudijus; Žeruolis, Darius; Karmazinaitė, Sabina (Baltic Journal of Political Science, 2015)
This article re-conceptualizes Europeanization with a development theory based approach to assess changes in Lithuania after the country’s 2004 European Union (EU) accession. The authors use the development theory of Douglass North, John Wallis, and Barry Weingast as a conceptual framework to highlight the role of Lithuania’s elite and to examine broader social transformations. This developmental framework focuses and complements the current theory of Europeanization and emphasizes the positive role of the EU in promoting Lithuania’s long-term structural changes. A developmental approach also allows for an analysis of corruption and state capture, which are becoming important yardsticks for assessing change in Central and Eastern Europe. The results of this application (including a survey of the elite) demonstrate that, in Lithuania, change was more limited after joining the EU than during the pre-accession years and that the country’s domestic actors have been slow to replace the EU’s policy agenda with their own initiatives.